Programa de orientação parental em Terapia Ocupacional para auxiliar o cuidador principal no cotidiano das famílias de crianças e adolescentes com Transtorno Opositor Desafiador - Bontempo, Kaíla da Silva (Universidade Federal de São Carlos, 2025)
Introduction: Children and adolescents with Oppositional Defiant Disorder (ODD) exhibit challenging, antisocial behaviors and difficulties with self-regulation, which compromise family routines and directly impact family members. Objective: To develop a parental guidance program in Occupational Therapy based on the analysis of caregivers’ profiles, their perceptions of the disorder’s impact on family life, the clinical conditions of children/adolescents with ODD, and the existing literature. Methodology: The research comprised three studies: Study 1 consisted of a literature review covering the last three years in the CAPES Portal, using English and Portuguese descriptors—“Oppositional Defiant Disorder,” “Family,” and “Occupational Therapy”—combined with the Boolean operator “and”; Study 2 analyzed the four profile of caregivers treated at a CAPSi through a descriptive-exploratory design, using standardized instruments to assess the behaviors of children and adolescents with ODD and parental sense of competence, as well as a semi-structured interview to explore the impact of symptoms on family routines; Study 3 involved the development of the PROPTO-ODD program through the integration of literature findings and data on caregivers’ daily lives, allowing contextual adjustments to the initial proposal. The program was organized into progressive modules with defined objectives, core content, practical activities, and support materials, based on three criteria: scientific relevance, practical pertinence to families’ real demands, and feasibility within Occupational Therapy. Results and Discussion: The systematic review (Study 1) identified 12 types of interventions for managing ODD, mostly centered on parent–child relationships and predominantly conducted by psychologists and psychiatrists, with varied approaches and an increasing focus on caregivers. Despite advances and growing interdisciplinarity, important gaps remain, particularly the lack of culturally adapted programs for the Brazilian context and the limited presence of Occupational Therapy. Study 2 showed that caregivers of children and adolescents with ODD treated at the CAPSi experience high physical and emotional burden, marked by socioeconomic vulnerability, low parental self-efficacy, and significant psychological distress. Symptom severity, coupled with limited support networks, intensifies caregiver burnout and restricts engagement in meaningful activities and self-care. Study 3 presents PROPTO-ODD as an original Occupational Therapy intervention focused on improving participation in meaningful family occupations. Final Considerations: Study 1 highlights critical gaps in the literature and underscores the need for contextualized programs; Study 2 emphasizes caregiver overload and low self-efficacy, reinforcing the importance of psychosocial support and daily routine reorganization; Study 3 introduces PROPTO-ODD as a unique Occupational Therapy contribution that integrates behavior management, routine restructuring, and activity-based therapeutic strategies. Together, the studies demonstrate the need for culturally sensitive and integrated interventions in the care of children and adolescents with ODD, considering symptoms, family dynamics, and social vulnerabilities. Thus, the program emerges as a powerful strategy to enhance care within the CAPSi by strengthening family bonds, autonomy, and daily practices in managing ODD.
Occupational Therapy parental guidance program to assist the primary caregiver in the daily lives of families of children and adolescents with Oppositional Defiant Disorder
Keywords: Adolescentes; Crianças; Famílias; Intervenção; Parentalidade; Práticas Parentais; Saúde Mental do Cuidador; Terapia Ocupacional; Transtorno Opositivo Desafiador; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar